Effect of different sampling locations on the antibacterial property of Centella asiatica leaves - Rasha Saad; Mohd Nazmi; Norfazrin Hanif; Fadli Asmani; Eddy Yusuf (International Journal of Pharmacy and Analytical Research, 2014)
An experiment was carried out to determine the effect of antibacterial activity of Centella asiatica herb collected from different sampling location. The effect can be determined by analysing the bacterial response towards plant extracts. The tested bacterial strains were Staphylococcus aureus, Bacillus subtilis, Escherichia coli and Salmonella typhi. Zone of inhibition produced by different extracts against the selected strains was measured and compared with standard antibiotic penicillin (10μg) and gentamicin (10μg). The result demonstrated that the Centella asiatica from urban area have higher antimicrobial activities (average of 1.629 cm zone of inhibition) than sub-urban (average of 1.305 cm zone of inhibition). All the extracts showed better results against the Escherichia coli strains comparing with penicillin (10μg) but not for gentamicin (10μg) test on the other bacteria strains. The results obtained in the present study suggest that the different extracts of Centella asiatica revealed a significant scope to develop a novel broad spectrum of antibacterial herbal formulations.